Data supporting: 'Fibre-optic measurement of strain and shape on a helicopter rotor blade during a ground run: data for the measurement of strain' - James, Stephen W.; Kissinger, Thomas; Weber, Simone; Mullaney, Kevin; Chehura, Edmon; Barrington, James; Tatam, Ralph P. (Cranfield University, 2022)
FBG_Data_CORD.csv contains the raw wavelength data from the 10 FBGs (G1-G10) recorded during the ground run detailed within the paper "Fibre-optic measurement of strain and shape on a helicopter rotor blade during a ground run - part 1: measurement of strain", James et al. Smart Materials and Structures, available online, May 2022. The unit of the "Time" column is seconds, while the units of columns G1-G10 are nanometers. FSI_Data_CORD.csv contains the raw phase data obtained from the interferometers formed between the reflectors (R1-R10,) and the cleaved end of the optical fibre, recorded during the ground run detailed within the paper The unit of the "Time" column is seconds, while the units of columns R1-R10 are radians.
Keywords: Optical Fibre Sensors'; 'Fibre Bragg Grating Sensors'; 'fibre segment interferometry'; 'Interferometry'; 'Strain measurement'; 'helicopters'; 'Rotor Blades'; 'Aerospace Engineering'; 'Aerospace Structures'; 'Photonics and Electro-Optical Engineering (excl. Communications)'; 'Optical Physics not elsewhere classified'; 'Photonics; Optoelectronics and Optical Communications'